Comparative quantum chemical and spectral characterization of meso-tetra(4-sulfonatophenyl) porphine forms as seeds for J- and H-aggregates - Laura Baliulyte; Darius Abramavicius; Saulius Bagdonas; Agne Kalnaityte; Vilius Poderys; Ricardas Rotomskis; Virginijus Barzda (AIP Advances, 2023)
Aggregation of 5,10,15,20-tetrakis(4-sulfonatophenyl) porphyrin (TPPS4) molecules as a function of solvent pH is a complex process because of the co-existence of many possible interacting monomeric ionic forms that self-assemble into various aggregate structures. Possible seeding elements of aggregates were studied using quantum chemical calculations based on density functional theory to determine favorable ionic forms and their dimers, and the simulated spectral characteristics were compared with the measured absorption spectra. Five different forms of TPPS4 monomers and ten dimers were found as possible candidates for aggregate precursors. It was found that monomeric forms dominate at pH = 12.1, pH = 7.1, pH = 4.1, and pH = 3.0 as well as at pH = −1.0. In contrast, J-type dimers become a dominant form at pH = 1.0.